Response Systems, Antagonistic Responses, and the Behavioral Repertoire - Ortu, Daniele; Bugg, Ryan M. (Frontiers in Behavioral Neuroscience, 2022)
While response systems are often mentioned in the behavioral and physiological literature, an explicit discussion of what response systems are is lacking. Here we argue that response systems can be understood as an interaction between anatomically constrained behavioral topographies occasioned by currently present stimuli and a history of reinforcement. “New” response systems can develop during the lifetime as the organism gains instrumental control of new fine-grained topographies. Within this framework, antagonistic responses compete within each response system based on environmental stimulation, and competition is resolved at the striatum-thalamo-cortical loops level. While response systems can be by definition independent from one another, separate systems are often recruited at the same time to engage in complex responses, which themselves may be selected by reinforcement as functional units.